2018
DOI: 10.1097/iae.0000000000001617
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography to Distinguish Choroidal Neovascularization From Macular Inflammatory Lesions in Multifocal Choroiditis

Abstract: The combined findings of conventional imaging and OCTA demonstrate distinctive features of inflammatory lesions and CNV in multifocal choroiditis, allowing an appropriate management of these sight-threatening lesions. However, OCTA alone did not distinguish between active and inactive CNVs and should be integrated into an MMI approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 18 publications
2
51
0
1
Order By: Relevance
“…A recently published study by Astroz et al looked only for subretinal or intraretinal fluid on FA and OCT in patients with MFC, prior to OCTA analysis. The authors did not observe a statistically significant difference in terms of morphological features such as collaterals, peripheral arcades and dark halo between active and inactive CNVs on OCTA 12. Similar to our results, Zahid et al reported that sub-RPE lesions did not reveal neovascular flow on OCTA.…”
Section: Discussionsupporting
confidence: 90%
“…A recently published study by Astroz et al looked only for subretinal or intraretinal fluid on FA and OCT in patients with MFC, prior to OCTA analysis. The authors did not observe a statistically significant difference in terms of morphological features such as collaterals, peripheral arcades and dark halo between active and inactive CNVs on OCTA 12. Similar to our results, Zahid et al reported that sub-RPE lesions did not reveal neovascular flow on OCTA.…”
Section: Discussionsupporting
confidence: 90%
“…However, dye leakage can occur from both iCVNs and non‐neovascular inflammatory foci (Figure A‐C). OCTA can clearly demonstrate the presence of the neovascular network forming the iCNV (Figure D), a feature that is not present in other types of lesions …”
Section: Oct/octa Of Inflammatory Choroidal Neovascularizationmentioning
confidence: 95%
“…In most OCTA scans, iCNV appears as a well‐circumscribed neovascular network, typically located at the level of the avascular zone (outer retina RPE) . Due to alterations in the normal anatomy of the retinal layers induced by the exudative process, the use of automated segmentation software can fail .…”
Section: Oct/octa Of Inflammatory Choroidal Neovascularizationmentioning
confidence: 99%
See 2 more Smart Citations